Employee Appreciation. The value of valuing people - Christopher Ruppel; Julia Stranzl; Sabine Einwiller; Jens Hagelstein; Ingrid Wahl; Karen Berger (Academic Society for Management & Communication, 2024)
Employee appreciation, as this two-year research project by the University of Vienna shows, is more than a nice-to-have. It's a necessity to attract and retain talent in today's competitive labor market. Employees who feel valued are more likely to remain engaged, motivated, and loyal to their organization. Executives and middle managers have a crucial role to play in creating an appreciative work environment. Internal communication can amplify appreciation efforts and help create a workplace in which every individual feels valued, supported, and empowered to thrive. The detailed research findings can be read in the Communication Insights: what kind of appreciation employees expect, the effects of appreciation for employees and the company as a whole, the role of managers and internal communication professionals in expressing appreciation. – – Ein zweijähriges Forschungsprojekt der Universität Wien zeigt, dass die Wertschätzung von Mitarbeitenden mehr als nur ein "Nice-to-have" ist. Sie ist unverzichtbar, um Talente im heutigen wettbewerbsintensiven Arbeitsmarkt zu gewinnen und zu halten. Mitarbeitende, die sich wertgeschätzt fühlen, sind eher engagiert, motiviert und loyal gegenüber ihrem Unternehmen. Führungskräfte und mittlere Managerinnen und Manager spielen dabei eine entscheidende Rolle. Eine effektive interne Kommunikation kann dazu beitragen, ein Arbeitsumfeld zu schaffen, in dem sich Mitarbeitende wertgeschätzt und unterstützt fühlen. Nähere Informationen zu den Forschungsergebnissen können in der Communication Insights nachgelesen werden: welche Art von Wertschätzung Mitarbeitende erwarten, welche Auswirkungen Wertschätzung auf Mitarbeitende und das gesamte Unternehmen hat und welche Rolle Kommunikationsverantwortlichen bei der Vermittlung von Wertschätzung einnehmen.
Keywords: 650